IMPLEMENTATION PROGRAM FOR AGRARIAN REFORM IN AGRARIAN REFORM VILLAGE IN BANGKA CENTRAL DISTRICT (CASE STUDY: CAMBAI SELATAN VILLAGE) - Hadi Fitriansyah; Ronald Sukwadi; Budi Kartadinata (Universitas Tidar, 2022)
Agrarian reform is defined as a process of reorganizing the structure of control, ownership, use, and utilization of land so that it is more equitable. The Agrarian Reform Village is expected to be a small-scale embodiment of the equal distribution of the structure of control, ownership, use, and utilization of land to improve social justice and community welfare. This study aims to analyze the implementation of Agrarian Reform activities in South Cambai Village as Agrarian Reform Village and analyze land that can be used as Land Object of Agrarian Reform potential. The method used in this research is descriptive and spatial analysis in determining the potential of Land Object of Agrarian Reform. The results of the analysis show that from 727 registered land parcels, 18% of the subjects receiving Land Object of Agrarian Reform work as farmers, and subjects receiving land for the agrarian reform object are indicated to have not been targeted. With the integration of asset management and access arrangement, the resulting impact is an increase in people's income. The potential of land that does not have strong legality is 900.96 hectares or with a percentage of 33% of the total area of ​​South Cambai Village.